FILSAFAT EKONOMI PANCASILA MUBYARTO - Hastangka, Hastangka (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2012)
The purposes of this paper is to find and analyze on Mubyarto’s philosophy of Pancasila Economics. Mubyarto is the great philosopher in Pancasila’s Economics. Conceptually, Pancasila’s Economics become fundamental aspects in Indonesia’s economics development paradigm. The issues on Mubyarto’s Pancasila’s Economics emerge when questioning economy growth, equality, and economy justice; and how Pancasila’s Economics can explains economics growth between industrial and agricultural principal. This paper discussed about the essence of Pancasila’s Economics, how it works, how Mubyarto’s theorizing Pancasila’s Economics into practice, and how does economists, and scholar’s responses on Pancasila Economics. Finally, we conclude that Mubyarto’s Pancasila’s Economics is an approach to see phenomena of economy in Indonesian society and Mubyarto’s Pancasila’s Economics is an alternative approach to learn economic against conservatism and neo-classical theory of economy.